Achieving High-Performance Spherical Natural Graphite Anode through a Modified Carbon Coating for Lithium-Ion Batteries - Hae-Jun Kwon; Sang-Wook Woo; Yong-Ju Lee; Je-Young Kim; Sung-Man Lee (Energies, 2021)
The electrochemical performance of modified natural graphite (MNG) and artificial graphite (AG) was investigated as a function of electrode density ranging from 1.55 to 1.7 g∙cm−3. The best performance was obtained at 1.55 g∙cm−3 and 1.60 g∙cm−3 for the AG and MNG electrodes, respectively. Both AG, at a density of 1.55 g∙cm−3, and MNG, at a density of 1.60 g∙cm−3, showed quite similar performance with regard to cycling stability and coulombic efficiency during cycling at 30 and 45 °C, while the MNG electrodes at a density of 1.60 g∙cm−3 and 1.7 g∙cm−3 showed better rate performance than the AG electrodes at a density of 1.55 g∙cm−3. The superior rate capability of MNG electrodes can be explained by the following effects: first, their spherical morphology and higher electrode density led to enhanced electrical conductivity. Second, for the MNG sample, favorable electrode tortuosity was retained and thus Li+ transport in the electrode pore was not significantly affected, even at high electrode densities of 1.60 g∙cm−3 and 1.7 g∙cm−3. MNG electrodes also exhibited a similar electrochemical swelling behavior to the AG electrodes.